2020
DOI: 10.1002/tea.21676
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between the Educative Teacher Performance Assessment and preservice teachers' pedagogical content knowledge

Abstract: This study examined the relationship between preservice teachers' Educative Teacher Performance Assessment (edTPA) scores, the most widely implemented preservice teacher performance assessment in the United States, and the pedagogical content knowledge (PCK) levels reflected in their edTPA portfolios. PCK is a specialized form of teacher professional knowledge widely considered a paramount construct of teacher quality. Thirty‐six preservice science teachers' PCK levels were determined by analyzing their edTPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 84 publications
(158 reference statements)
1
14
0
4
Order By: Relevance
“…Furthermore, OTS and KSU components were at the center. This result confirms the results of similar studies on the nature of the interaction among PCK components (Park & Chen, 2012;Reynolds & Park, 2021;Suh & Park, 2017). Although learning and teaching experiences did not lead to an explicit change in terms of PCK interaction, it was revealed that the connection between OTS-KSU, KSU-KISR and KSU-KAS was strengthened at the end of the course.…”
Section: The Effect Of Learning and Teaching Experiencessupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, OTS and KSU components were at the center. This result confirms the results of similar studies on the nature of the interaction among PCK components (Park & Chen, 2012;Reynolds & Park, 2021;Suh & Park, 2017). Although learning and teaching experiences did not lead to an explicit change in terms of PCK interaction, it was revealed that the connection between OTS-KSU, KSU-KISR and KSU-KAS was strengthened at the end of the course.…”
Section: The Effect Of Learning and Teaching Experiencessupporting
confidence: 88%
“…Furthermore, it was observed that learning and teaching experiences increased the importance of the KSU component in particular Ali Yiğit Kutluca Sosyobilimsel argümantasyona yönelik pedagojik alan bilgisi (PAB) bileşenlerinin etkileşimindeki değişimin incelenmesi: Deneyimlerin etkisi (Park & Oliver. 2008b;Reynolds & Park, 2021). This development may contribute to teachers in terms of understanding student potential, responding to different ideas and considering personal perspectives (Sadler, 2006;McNeill & Pimentel, 2010).…”
Section: The Effect Of Learning and Teaching Experiencesmentioning
confidence: 97%
See 2 more Smart Citations
“…As evidenced by decades of this journal's published research, the teaching and learning of science is often a specialized affair (e.g. Anderson, 2000; Feldman et al, 2009; Gawley, 1965; Reynolds & Park, 2021; Rutt et al, 2021). Someone who has an advanced understanding of their science subject matter along with a sense of how they intend to teach it, coupled with the ability and willingness to teach in a secondary science classroom, is someone who deserves the attention and care of our field.…”
Section: Introductionmentioning
confidence: 99%